Causing Factors in Speaking Ability of Students at SMK Satu Nusa 2 Bandar Lampung - Swarastuti, Astirini; Sutiwi, Sri; Prasetyo, Rizki Tri (Attractive : Innovative Education Journal, 2024)
This research was made based on the problems at SMK Satu Nusa 2 Bandar Lampung. The writers found the lack of speaking mastery in students and decided to do research related to the factors that affect students' speaking mastery. This research uses qualitative research methods and finally found several factors that affect students' interest in speaking English, namely, mother tongue influence factor, weak mastery of English grammar factor, minimal vocabulary factor, teaching method factor, environmental factor, lack of learning motivation, factors affecting technological development, and psychological factors. Keywords: Speaking Ability, Grammar, Vocabulary, Technological Development